2018
DOI: 10.1177/0194599818770621
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis of Sinonasal Lymphoma and Squamous Cell Carcinoma on CT, MRI, and PET/CT

Abstract: Objective The purpose of this study was to analyze computed tomography (CT) and magnetic resonance (MR) images and to evaluate the maximum standardized uptake value (SUV max) of positron emission tomography (PET)/CT parameters between sinonasal non-Hodgkin's lymphoma (NHL) and squamous cell carcinoma (SCC), knowing the imaging features that distinguish sinonasal NHL from SCC. Study Design Case series with chart review. Setting University tertiary care facility. Subjects and Methods We analyzed the features on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 14 publications
7
35
1
Order By: Relevance
“…Magnetic resonance imaging (MRI) has been proven to play crucial roles in the differential diagnosis of sinonasal tumors [ 10 , 11 ], especially for classification of the lymphoma and squamous cell carcinoma [ 12 14 ]. Previous studies reported that the homogenous signal intensity, facial soft tissue involvement, and low ADC values on MR findings suggested the diagnosis of the lymphomas [ 12 14 ]. However, whether these features can help in differential diagnosis of lymphoma subtypes is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) has been proven to play crucial roles in the differential diagnosis of sinonasal tumors [ 10 , 11 ], especially for classification of the lymphoma and squamous cell carcinoma [ 12 14 ]. Previous studies reported that the homogenous signal intensity, facial soft tissue involvement, and low ADC values on MR findings suggested the diagnosis of the lymphomas [ 12 14 ]. However, whether these features can help in differential diagnosis of lymphoma subtypes is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…4 In the sinonasal cavity, lymphomas are thought to yield larger tumor volume with more homogeneous signal intensity and less intratumoral necrosis than SCC. 14,15 These findings may be associated with a prolonged hypoxic microenvironment in SCC and consequent tumor necrosis. 16 In addition, several studies have discriminated between SCC and lymphoma with advanced MR imaging techniques, such as diffusion and perfusion MR imaging.…”
Section: Squamous Cell Carcinoma and Lymphoma Of The Oropharynx: Diffmentioning
confidence: 99%
“…Radiologists obtain the information from intrinsic tumor characteristics and from other associated imaging features, such as tumor growth patterns, adjacent structural changes, and metastatic lymph node appearance. For example, adjacent bone destruction is more prominent in SCC than in lymphoma, 14 and central necrosis is one of the characteristic findings of metastatic lymph nodes from SCC. 15 Therefore, additional radiomics information obtained from the intrinsic tumor appearance would be useful to improve the diagnostic performance of radiologists.…”
Section: Squamous Cell Carcinoma and Lymphoma Of The Oropharynx: Diffmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignancies of the sinonasal cavity are associated with substantially greater heterogeneity compared to malignancies of the upper aerodigestive tract, where squamous-cell carcinoma (SCC) predominates. 1 Even though SCC is the most frequent sinonasal neoplasm, 2 there exists a growing variety of some other histologies, such as tumors of epithelial, neuroectodermal, mesenchymal, and lymphoproliferative lineage. Probably the most challenging diagnostic category of sinonasal malignancies is the small round blue cell tumor (SRBCT), which constitutes a heterogeneous group of malignant neoplasms characterized by undifferentiated tumor cells with small-sized nuclei and scant cytoplasm.…”
Section: Introductionmentioning
confidence: 99%